2021
DOI: 10.1177/10499091211042837
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Awareness of Advanced Disease Status, Psychological Distress and Quality of Life Among Patients With Advanced Cancer: Results From the APPROACH Study, India

Abstract: Background: Prognostic disclosure to patients with advanced cancer facilitates treatment decisions and goals of care discussions. However, the perspectives of patients, families and physicians differ in this regard across different cultures. Non-disclosure of cancer diagnosis or prognosis is commonly observed in family-centric cultures such as India. Aim: To assess the prevalence of and factors associated with cancer patients’ awareness of advanced disease status; and its with quality of life and psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…These cities are no less urban than the other study sites. We postulate that this may be explained by low levels of patient awareness of disease and its severity in India, as have been previously reported 9,38 …”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…These cities are no less urban than the other study sites. We postulate that this may be explained by low levels of patient awareness of disease and its severity in India, as have been previously reported 9,38 …”
Section: Discussionmentioning
confidence: 64%
“…We postulate that this may be explained by low levels of patient awareness of disease and its severity in India, as have been previously reported. 9,38 This study found that previously engaging in smoking or drinking when they were aware of the cancer-associated risks were significantly associated to perceived stigma. We were able to clearly show that using alcohol/tobacco without knowledge of the health risks was not significantly associated with perceived stigma.…”
Section: Discussionmentioning
confidence: 79%
“…Future modification may also include the option of family sitting in for the ENABLE-SG sessions with patients. This may reassure family who wish to protect their loved one from unnecessary exposure to "negative" thoughts; however, the family's presence may also steer discussions away from prognostic awareness which is believed to worsen patient quality of life and mood (Satija et al 2022;Wynn Mon et al 2021). With regard to planning a larger scale trial to evaluate the effectiveness of ENABLE-SG on patient outcomes, the sample size should adequately account for the substantial non-completion rate of patient-reported outcome measures at follow-up time points.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the multisite APPROACH protocol, we aimed to recruit a sample of 200 participants. 20 , 21 To obtain this sample size, 473 patients were assessed for eligibility via daily screening of medical records of outpatients seen at the medical oncology and palliative care departments and inpatient medical and surgical wards and referrals from nurses and patient. Of the pool of patients, 266 were deemed ineligible based on medical record review or after being approached for the study or declined to participate.…”
Section: Research Methods and Designmentioning
confidence: 99%